Effect of Counterface Roughness on the Wear of Polyoximethylene and Polypropylene - Aksulu, Murat; Palabiyik, Mehmet (ASMEDC, 2008)
In this study, effect of counterface roughness on dry sliding wear of polyoximethylene (POM) and polypropylene (PP) against stainless steel discs (HRC 52) is investigated. A pad on disc tribotester was used. Cylindrical surfaces of discs were used as wearing surfaces. Polymer specimens were produced as cylindrical pins. One of end faces of each pin was formed in the same radius of the discs. Normal force and sliding speed were constant. Roughness of the discs was produced by cylindrical grinding. Very low roughness values (mean of profile deviations Ra < 0.15 μm) were produced by using SiC emery paper after grinding. Ra parameters of the discs were measured both in axial (perpandicular to grinding traces) and circumferential direction (parallel to grinding traces). Average radius of curvature of the asperities Rav was computed by numerical analysis using raw surface profile data obtained from roughness measurements. Axial roughness measurements were chosen to illustrate the variation of wear rate and coefficient of friction with counterface roughness. Axial Ra values were varying from almost 0.1 – 3 μm. Disc surfaces were observed using an optical microscope. Worn polymer pin surfaces were observed by a Scanning electron microscope (SEM) to investigate wear mechanisms. SEM micro-photographs of the pins which worked against counterfaces with an axial roughness Ra = 0.3 μm and Ra = 3 μm were taken. As a result, it was seen that steady state wear rates of POM and PP increase with increasing disc surface roughness, and that circumferential Ra parameter may be effective to explain the interesting variation of wear rate with axial Ra, for axial Ra = 1–2.5 μm. PP and POM were observed to form no transfer film on the counterfaces. According to the SEM micro-photographs, for axial Ra = 0.3 μm some fatigue cracks were observed on the wear surface of the POM pins. For axial Ra = 3 μm, for both polymers, traces which were evident of abrasive wear, tearing and wear debris which was irregularly shaped particles were observed. It was investigated whether the relationship between wear rate and Rav conforms to the “fatigue wear model” of Hollander and Lancaster. In this investigation, asperities on the disc surfaces were assumed to have hemi-cylindrical shape and the radius of the hemi-cylinder is taken as Rav calculated from axial roughness profiles. It was seen that the results obtained for axial Ra = 0.1–1 μm, conform to the fatigue wear model.